Efecto de la harina de hojas de guayaba (psidium guajava l.) Como aditivo fitobiótico en dietas para pollos pio pio durante la etapa inicial - Arias López, Ivis Nayely (2024)
In Ecuador, poultry production is one of the most important productive activities of the Ecuadorian economy, based mainly on two productive sectors: commercial chicken and egg production. The objective of this study was to evaluate the effect of guava leaf flour as phytobiotic additives in diets for pio pio chickens in the initial stage. The study was carried out in the María Ester facility belonging to the El Empalme canton of the province of Guayas. A Completely Randomized Design (DCA) was used with four treatments and five repetitions (1m2 divisions). The treatments were based on diets that included guava leaf flour as a phytobiotic, being T1 (0%), T2 (0.5%), T3 (1.0%) and T4 (1.5%). The data were subjected to Tukey's multiple range test (P˃0.05), and a total of 140 pio pio chickens were used. The variables analyzed included food characteristics (%), feed consumption (g), weight gain (g), feed conversion (g), mortality (%) and economic analysis. The results obtained in the bromatological analyzes T4 (1.5%) stood out with the maximum percentage of 44.92% of fiber and fat with 7.86%. Food consumption, no significant differences were found. While, in weight gain and feed conversion statistical differences were observed. On the other hand, the economic analysis in Q3 (1.0%) exhibited the highest benefit/cost ratio with $1.71. Therefore, at 14 days of age, the group fed with 1.5% guava leaf meal showed a significantly greater weight gain of 153.86 g, and a lower feed conversion rate of 2.32 g.